Oxazolidinones: Are they only good for the discovery of antibiotics? A worm's eye view - Pathania Shelly; Petrova-Szczasiuk Kseniia; Pentikäinen Olli; Singh Pankaj Kumar (Elsevier B.V., 2025)
Oxazolidinones are one of the well-known classes of O-heterocycles which has yielded various potent antibiotics. Several oxazolidinone-based antibiotics are either FDA-approved or are in clinical trials. They act via competitively binding to the 23S rRNA, leading to the inhibition of bacterial protein synthesis. However, this work is an attempt to analyze the other side of oxazolidinone-based pharmacological profile. Herein, we have studied, if most of the recently reported oxazolidinone derivatives are antibiotics, and if so, what are other possible pharmacological profiles attributed to them? And how there is an inadvertent bias to consider oxazolidinones only to design and develop antibiotics. We have attempted to understand and explain the difference between structural and/or pharmacophoric features of potent oxazolidinone-based antimicrobials and other pharmacological profiles. We have highlighted the unused pharmacophoric spaces available in this core, which could be explored to diversify the pharmacological space of this heterocyclic core. This work could provide a crucial realization of bias towards oxazolidinone in drug discovery attempts, which restricts it only to be a core for antibiotics and can promote its use to hit other therapeutic targets.